Exchange-Rate-Based Stabilization under Imperfect Credibility - Calvo, Guillermo; Vegh Gramont, Carlos (Washington, D.C. : International Monetary Fund, 1991)
This paper analyzes stabilization policy under predetermined exchange rates in a cash-in-advance, staggered-prices model. Under full credibility, a reduction in the rate of devaluation results in an immediate and permanent reduction in the inflation rate, with no effect on output or consumption. In contrast, a non-credible stabilization results in an initial expansion of output, followed by a later recession. The inflation rate of home goods remains above the rate of devaluation throughout the program, thus resulting in a sustained real exchange rate appreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet